On the Influence of the Malting and Brewing Process on the Amounts of Pronyl-L-Lysine, a Chemopreventive and Antioxidant Maillard Product in Melanoidins - Spieleder, Elmar; Krottenthaler, Martin; Back, Werner; Frank, Oliver; Lenczyk, Marlies; Thomas Hofmann, Thomas Hofmann (BrewingScience, 2006)
The influence of the type of malt, the malting procedure, as well as the brewing process on the amounts of the antioxidant and Phase II-Enzyme modulating, protein-bound 2,4-dihydroxy-2,5-dimethyl-1-(5-acetamino-5-methoxycarbonyl-pentyl)-3-oxo-2H-pyrrol, known as pronyl-L-lysine, in malts and beers was investigated in quantitative studies. These studies revealed a strong influence of both the malting and brewing processes on the contents of the chemopreventive target compound in the final products. This knowledge might be helpful to systematically increase of the amounts of the bioactive, protein-bound pronyl-L-lysine in beer and beer containing beverages by technological means.